Identification of pyrC gene as an immunosuppressive factor in Francisella novicida infection - Nakamura, Takemasa; Shimizu, Takashi; Ikegaya, Ryo; Uda, Akihiko; Watanabe, Kenta; Watarai, Masahisa (Frontiers in Cellular and Infection Microbiology, 2022)
Francisella tularensis, a bacterial causative agent of the zoonosis tularemia, is highly pathogenic to humans. The pathogenicity of this bacterium is characterized by intracellular growth in immune cells, like macrophages, and host immune suppression. However, the detailed mechanism of immune suppression by F. tularensis is still unclear. To identify the key factors causing Francisella-mediated immunosuppression, large-scale screening using a transposon random mutant library containing 3552 mutant strains of F. tularensis subsp. novicida (F. novicida) was performed. Thirteen mutants that caused stronger tumor necrosis factor (TNF)-α production in infected U937 human macrophage cells than the wild-type F. novicida strain were isolated. Sequencing analysis of transposon insertion sites revealed 10 genes, including six novel genes, as immunosuppressive factors of Francisella. Among these, the relationship of the pyrC gene, which encodes dihydroorotase in the pyrimidine biosynthesis pathway, with Francisella-mediated immunosuppression was investigated. The pyrC deletion mutant strain (ΔpyrC) induced higher TNF-α production in U937 host cells than the wild-type F. novicida strain. The ΔpyrC mutant strain was also found to enhance host interleukin-1β and interferon (IFN)-β production. The heat-inactivated ΔpyrC mutant strain could not induce host TNF-α production. Moreover, the production of IFN-β resulting from ΔpyrC infection in U937 cells was repressed upon treatment with the stimulator of interferon genes (STING)-specific inhibitor, H-151. These results suggest that pyrC is related to the immunosuppressive activity and pathogenicity of Francisella via the STING pathway.